Effect of Pin Diameters on the Wear Characteristics of Friction Pairs - Wei, Y.H.; Wang, X.L.; Liu, Y.P.; Chen, L.J. (Проблемы прочности, 2019)
The tribological tests are carried out to assess the effect of pin diameters on wear characteristics via changing contact stresses and sliding speeds to provide support for choosing friction pair sizes. The friction couple is set as CuZn pins for medium carbon steel (No. 1045 steel) rings. The differential wear rate and its calculation formula are defined to express the line wear rate or the wear resistance of unit cross-section area. The effect of the pin end surface diameter on differential wear rate and its scale/increased multiplier are investigated. When the product (P×V=0.095) is kept constant, the abrasion loss for the specimens of a small diameter (d1=0.6 mm) is lesser than that of the specimens of a large diameter (d2=4.0 mm). As compared to the sliding speed, the change in contact stresses exerts a greater influence on the wear behavior, especially for small-diameter specimens. The differential wear rate of small-diameter specimens is always higher than that of the specimens of a large diameter. The scale multiplier of the differential wear rate is always larger than that of the contact pressure stress, especially for small-diameter specimens. С целью обоснования выбора размеров пар трения проводятся трибологические испытания по оценке влияния диаметров штифта на характеристики износа путем изменения нагрузок и скорости скольжения. Пара трения представляется в виде штифтов из CuZn к кольцам из среднеуглеродистой стали (сталь 1045). Дифференциальная скорость изнашивания и формула для ее расчета определяются для выражения линейной скорости изнашивания или сопротивления износу единицы площади поперечного сечения. Исследуются влияние различного диаметра торцевой поверхности штифтов, дифференциальная скорость изнашивания и ее увеличенный множитель. Результаты показывают, что при поддержании постоянства произведения P×V=0,095 потери при истирании образцов малого диаметра (d1=0,6 мм) меньше, чем образцов большого диаметра (d2 =4,0 мм). По сравнению со скоростью скольжения изменение нагрузки более существенно влияет на характеристики износа, особенно для образцов малого диаметра. Дифференциальная скорость изнашивания образцов малого диаметра всегда больше, чем образцов большого диаметра. Увеличенный множитель дифференциальной скорости изнашивания всегда превышает увеличенный множитель повышения напряжения контактного давления, особенно для образцов малого диаметра. З метою обґрунтування вибору розмірів пар тертя проводяться трибологичні випробування з оцінки впливу діаметрів штифта на характеристики зносу шляхом зміни навантажень і швидкості ковзання. Пара тертя представляється у вигляді штифтів з СuZn до кілець з середньовуглецевої сталі (сталь 1045). Диференціальна швидкість зношування і формула для її розрахунку визначаються для вираження лінійної швидкості зношування або опору зносу одиниці площі поперечного перерізу. Досліджуються вплив різного діаметру торцевої поверхні штифтів, диференціальна швидкість зношування і її збільшений множник. Результати показують, що при підтримці сталості Р x V = 0,095 втрати при стиранні зразків малого діаметра (d1 = 0,6 мм) менше, ніж зразків великого діаметра (d2 = 4,0 мм). У порівнянні зі швидкістю ковзання зміна навантаження більш істотно впливає на характеристики зносу, особливо для зразків малого діаметра. Диференціальна швидкість зношування зразків малого діаметра завжди більше, ніж зразків великого діаметру. Збільшений множник диференціальної швидкості зношування завжди перевищує збільшений множник підвищення напружень контактного тиску, особливо для зразків малого діаметра.